The improvement of dampening solution for offset printing - Velychko, Olena; Zolotukhina, Каteryna; Rozum, Tatiana (Eastern-European Journal of Enterprise Technologies, 2016)
Experimental models of dampening fluids with antibacterial additives are developed. The influence of additives on the change in conductivity and acidity of dampening fluids and stability characteristics during operation and storage are studied. Methods of processing dampening fluids to improve their performance level and quality of the final printed product are studied. The work reveals some new facts about the characteristics for printability such as influences of dampening solution’s additives on the color characteristics of imprints. The material is devoted to the study of complex technological environment interference parameters printed contact and method of stabilization for the normalization of quality reproduction images of porous and nonadsorbent materials. There were grounded technological parameters of stable color reproduction by minimizing the ratio of ink transferring on nonadsorbent and porous materials. There were developed for a special purpose additions to regulate the offset printing process and method of their introduction into the technology environment and its control that allows to improve the quality of printed production. The effect of technological environment components on stability of printing process has been determined.